Combination of Antibodies and Antibiotics as a Promising Strategy Against Multidrug-Resistant Pathogens of the Respiratory Tract - Domenech, Mirian; Sempere, Julio; de Miguel, Sara; Yuste, Jose (Frontiers in Immunology, 2018)
The emergence of clinical isolates associated to multidrug resistance is a serious threat worldwide in terms of public health since complicates the success of the antibiotic treatment and the resolution of the infectious process. This is of great concern in pathogens affecting the lower respiratory tract as these infections are one of the major causes of mortality in children and adults. In most cases where the respiratory pathogen is associated to multidrug-resistance, antimicrobial concentrations both in serum and at the site of infection may be insufficient and the resolution of the infection depends on the interaction of the invading pathogen with the host immune response. The outcome of these infections largely depends on the susceptibility of the pathogen to the antibiotic treatment, although the humoral and cellular immune responses also play an important role in this process. Hence, prophylactic measures or even immunotherapy are alternatives against these multi-resistant pathogens. In this sense, specific antibodies and antibiotics may act concomitantly against the respiratory pathogen. Alteration of cell surface structures by antimicrobial drugs even at sub-inhibitory concentrations might result in greater exposure of microbial ligands that are normally hidden or hardly exposed. This alteration of the bacterial envelope may stimulate opsonization by natural and/or specific antibodies or even by host defense components, increasing the recognition of the microbial pathogen by circulating phagocytes. In this review we will explain the most relevant studies, where vaccination or the use of monoclonal antibodies in combination with antimicrobial treatment has demonstrated to be an alternative strategy to overcome the impact of multidrug resistance in respiratory pathogens.